A Model of Human Resource Management System Suitable for the New Generation Z in Executive Organizations with Thematic Analysis Approach - Moein Pourahmadi; Saeed Jafarinia; Yusuf Vakili; Akbar Hasanpour (مدیریت دولتی)
Objective The continuity of a society is ensured by the process of socialization that transfers the social traditions of previous generations to new generations; that is, new generations never exactly repeat the social life of their predecessors step by step, but are always accompanied by criticism of some aspects of tradition or innovation. The new generation that organizations are facing today, and must prepare for, is Generation Z. Currently, there are different generations of employees in workplaces, each with its own characteristics, values, and behaviors. Effectively managing these generations is a fundamental challenge for organizations. Therefore, managers must both understand the individual characteristics of this generation and know how to manage them effectively. Without an appropriate organizational context for the activities and actions of Generation Z, human resource management programs are doomed to fail. The purpose of this research is to identify the key indicators of the new generation through a thematic analysis approach. Methods This research is qualitative and applied. Its participants are human resource specialists and experts from academic and government organizations who were determined through theoretical and snowball sampling methods. To identify the components of human resource practices for Generation Z employees in government organizations, semi-structured interviews were conducted, involving in-depth discussions with 50 human resource experts from academic and government organizations. Clark and Brown's content analysis method was used to analyze the data. Results Data analysis resulted in the formation of 506 initial codes, 30 sub-themes, and 9 main themes including individual/personality-work characteristics, psychological-health characteristics, job-employee characteristics, internal-external environment characteristics, solidarity-team building, cultural-social characteristics, job-oriented payment, person-oriented payment, justice-oriented payment, criteria-programs, justice-oriented evaluation, evaluation-feedback components, monitoring-strategic control, behavioral characteristics-teacher expertise, needs assessment-educational survey, flexibility-educational methods, educational styles-learning, database-scientific, IT services, equipment-infrastructure, recruitment-recruitment, strategy-oriented planning, human-technical capital perspective, creativity-innovation perspective, needs assessment/survey of organizational demands-employees, ethical-behavioral characteristics of the manager, structural-executive goals, managerial capabilities, and legal-executive requirements in executive organizations. Conclusion Retaining and maintaining Generation Z human resources is one of the secrets to the success of any business. Effective managers believe that retaining and maintaining Generation Z employees is crucial for customer satisfaction, increased retention, and business satisfaction in government organizations. Generation Z easily moves between different organizations if the organization cannot provide them with the necessary motivation. They then have to bear the costs of continuous relocation and migration of human resources, along with other ancillary costs, including the cost of retraining and the cost of reduced efficiency and effectiveness. The results of this study showed that if the human resources model for Generation Z is applied in government organizations, it can greatly assist managers and government organizations in developing and improving the workforce, especially the new generation, turning them into leading organizations in their field.